2014
DOI: 10.1016/j.wem.2014.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Human Skeletal Muscle mRNA Response to a Single Hypoxic Exercise Bout

Abstract: The improvements in mitochondrial function reported with intermittent hypoxic training may not be explained by a single acute hypoxic exposure, and thus it appears that a longer period of preacclimatization than a single exposure may be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 12 publications
3
16
0
Order By: Relevance
“…In a previous human study, 1 hour of moderate-intensity cycling (60% of cycling peak power output) at simulated altitude (3000 m) had no effect on PGC-1a mRNA in the skeletal muscle of recreationally active men. 72 In agreement, PGC-1a total and isoform mRNA levels were unaffected by systemic hypoxia (3250 m) in the present study, despite deoxygenated HHb was matched between the BFR and HYP condition ( Figure 4A). Thus, the severity of exercise-induced muscle hypoxia was not decisive for the effects of BFR on PGC-1a levels in the present study.…”
Section: Augmented Pgc-1a-isoform Mrna Content After Blood Flow-ressupporting
confidence: 88%
“…In a previous human study, 1 hour of moderate-intensity cycling (60% of cycling peak power output) at simulated altitude (3000 m) had no effect on PGC-1a mRNA in the skeletal muscle of recreationally active men. 72 In agreement, PGC-1a total and isoform mRNA levels were unaffected by systemic hypoxia (3250 m) in the present study, despite deoxygenated HHb was matched between the BFR and HYP condition ( Figure 4A). Thus, the severity of exercise-induced muscle hypoxia was not decisive for the effects of BFR on PGC-1a levels in the present study.…”
Section: Augmented Pgc-1a-isoform Mrna Content After Blood Flow-ressupporting
confidence: 88%
“…This is consistent with a previous human study, in which contraction-stimulated increases in leg muscle PGC-1α mRNA content was unaffected by promoted systemic levels of epinephrine and lactate invoked by simultaneous arm exercise (Brandt et al, 2016). The present observation of unaltered PGC-1α levels after exercise in systemic hypoxia agrees with a previous human study that reported unchanged PGC-1α mRNA content after a single exercise session at simulated altitude (3000 m) in recreationally active men (Slivka et al, 2014). Since deoxygenated HHb was similar during exercise with ischaemia and in systemic hypoxia (Fig.…”
Section: Increases In Human Muscle Pgc-1α-isoform Mrna Content Are Unsupporting
confidence: 93%
“…Finally, these investigations should be conducted in well-defined populations in order to minimize confounding outcomes from heterogeneous participant groups that often result from convenience sampling. These recommendations are essential for understanding highly variable tissue level responses that are sensitive to fitness level and exercise habituation (Mounier et al 2009;Slivka et al 2014;Peters et al 2015).…”
Section: Altitude Considerations For Living and Trainingmentioning
confidence: 99%
“…Recent examination of mitochondrial biogenesis gene transcripts in human vastus lateralis obtained following an acute bout of hypoxic exercise reinforces the notion that adaptive responses to high altitude exercise are redox sensitive (Slivka et al . ). Nonetheless, human performance studies of hypoxic exercise on sea level performance are equivocal (Ventura et al .…”
Section: Introductionmentioning
confidence: 97%